Modification of Starch via the Biginelli Multicomponent Reaction. Issue 1 (13th September 2019) - Esen, Eren; Meier, Michael A. R.
Abstract: An efficient and straightforward modification of starch using renewable and commercially available aromatic aldehydes (benzaldehyde, vanillin, and p ‐anisaldehyde) and urea via the Biginelli multicomponent reaction is reported in this work. First, starch acetoacetate (SAA ) with a degree of substitution ranging from 1.4 to 2.5, depending on the reaction time or the molar ratio of reactants, is prepared. SAA is then modified with different aromatic aldehydes and urea via the Biginelli reaction. The modified products are characterized by ATR‐IR, NMR, and gel permeation chromatography (GPC). The processability of the products is also investigated using a hot press instrument, revealing that glycerol is a suitable and renewable plasticizer for the Biginelli products. Abstract : The modification of starch via Biginelli multicomponent reactions is described, yielding fully renewable materials. After characterizing the synthesized products in detail, glycerol is identified as a suitable plasticizer for the obtained very brittle polymers. Thus, a first insight into a possible processing route as well as the obtainable material properties are described.